1990
DOI: 10.1002/jbt.2570050104
|View full text |Cite
|
Sign up to set email alerts
|

Niacin attenuates bleomycin‐induced lung fibrosis in the hamster

Abstract: Bleomycin (BLM)-induced lung fibrosis has been shown to be accompanied by the activation of poly(ADP-ribose) polymerase and depletion of nicotinamide adenine dinucleotide (NAD) in the lung. Niacin, a precursor of NAD, was used in the present study to investigate its possible ameliorating effect on BLM-induced pulmonary fibrosis in hamsters. Niacin (500 mg/kg IP) or saline (IP) was injected daily for 16 or 23 days. On day 3, hamsters were treated with BLM (7.5 U/5 mL/kg) or an equivalent volume of saline intrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…Next, we examined the effect of niacin on zymosan-induced peritonitis in mice. Niacin (600 mg/kg) (Wang et al, 1990;Nagai et al, 1994;Godin et al, 2012) was administered to mice 24 hours after zymosan challenge ( Fig. 2A), and peritoneal macrophages were isolated for geneexpression analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we examined the effect of niacin on zymosan-induced peritonitis in mice. Niacin (600 mg/kg) (Wang et al, 1990;Nagai et al, 1994;Godin et al, 2012) was administered to mice 24 hours after zymosan challenge ( Fig. 2A), and peritoneal macrophages were isolated for geneexpression analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally believed that niacin offers protection against tissue damage caused by a variety of oxidants by virtue of its ability to increase intracellular level of NAD and to inhibit overactivation of poly(ADP-ribose) polymerase (79,81). An overstimulation of this chromosomal enzyme leads to intracellular depletion of NAD (82).…”
Section: Discussionmentioning
confidence: 99%
“…The hamsters were randomly placed into four treatment groups: saline-instilled fed control diet (SA), bleomycin-instilled fed control diet (BL), bleomycin-instilled fed taurine-niacin in diet (TNBL), and saline-instilled fed taurine-niacin in diet (TNSA). The animals were intratracheally instilled with either three consecutive doses of bleomycin sulfate in saline, or saline 1 week apart (2.5, 2.0, and 1.5 U/5 ml/kg) under pentobarbital anesthesia (75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85) mg/kg) as described by Zia et al (14).…”
Section: Methodsmentioning
confidence: 99%
“…Although rat lung NAD + levels are less than half of that in the liver [33], and although the PAR response to hyperoxia was blunted by niacin deficiency, there was no change in the measures of tissue injury due to niacin deficiency [13], suggesting that the decrease in PAR formation was not great enough to sensitize the lung to oxidant injury. Studies with more acute lung injury, using bleomycin, have shown that niacin supplementation, above requirement, can be protective [34].…”
Section: Liver and Lungmentioning
confidence: 99%